2020
DOI: 10.1063/1.5132376
|View full text |Cite
|
Sign up to set email alerts
|

Role of point and line defects on the electronic structure of LaAlO3/SrTiO3 interfaces

Abstract: Realization of heterostructures containing multiple two-dimensional electron liquids requires a fine control of the fabrication process. Here, we report a structural and spectroscopy study of LaAlO3/SrTiO3/LaAlO3 trilayers grown on the SrTiO3 substrate by pulsed-laser deposition. Scanning transmission electron microscopy with the help of ab initio calculations reveals that antisite defects associated with oxygen vacancies are primarily present in the SrTiO3 film (STO-f) close to the p-type interface (STO-f/LaA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Compared to the aforementioned techniques, an atomic-resolution electron probe is used to scan the films under study and the transmitted electrons are collected by multiple detectors, each one providing complementary structural, chemical, and electronic information. STEM-EELS has already been demonstrated to be a powerful tool that can identify electronic state modulations occurring in specific lattice positions of transition metal oxide heterostructures. For instance, this technique enabled the identification of local valence modulations occurring at the interfaces of LaNiO 3 -based heterostructures induced by charge transfer effects. ,, In our study, however, since the Ni valence changes neither across the MIT nor from one nickelate compound to another, we also do not expect it to vary across the different electronic domains. Our approach is instead based on locally assessing electronic properties by looking at specific fingerprints, buried in the O K and Ni L edge fine structures, which are characteristic of the distinct electronic phases, as previously observed in X-ray absorption spectroscopy (XAS) experiments. ,, Here we demonstrate that this is possible, reaching around 3.5 Å spatial resolution.…”
mentioning
confidence: 76%
“…Compared to the aforementioned techniques, an atomic-resolution electron probe is used to scan the films under study and the transmitted electrons are collected by multiple detectors, each one providing complementary structural, chemical, and electronic information. STEM-EELS has already been demonstrated to be a powerful tool that can identify electronic state modulations occurring in specific lattice positions of transition metal oxide heterostructures. For instance, this technique enabled the identification of local valence modulations occurring at the interfaces of LaNiO 3 -based heterostructures induced by charge transfer effects. ,, In our study, however, since the Ni valence changes neither across the MIT nor from one nickelate compound to another, we also do not expect it to vary across the different electronic domains. Our approach is instead based on locally assessing electronic properties by looking at specific fingerprints, buried in the O K and Ni L edge fine structures, which are characteristic of the distinct electronic phases, as previously observed in X-ray absorption spectroscopy (XAS) experiments. ,, Here we demonstrate that this is possible, reaching around 3.5 Å spatial resolution.…”
mentioning
confidence: 76%
“…For example, A. Kalabukhov et al observed the impact of oxygen vacancies on the electrical properties using cathode and photoluminescence techniques. 52 N. Palina et al showed oxygen orbital states using X-ray spectroscopies, 44 A. Gloter et al observed the distribution of point defects at the interface using scanning transmission electron microscopy 53 and G. Yuan et al reported on the behavior of oxygen vacancies at the LaAlO3/SrTiO3 heterostrucutre using positron annihilation spectroscopy. 54 In our work we extracted defect properties that cannot be accessed using these methods, such as the activation energies and capture cross-sections of the defect states using Deep-Level Transient Fourier Spectroscopy (DLTFS).…”
Section: Confidentialmentioning
confidence: 99%
“…The highly complex interplay of local defect structure and strongly confined electronic structure can induce multiple electronic and ionic phenomena at oxide interfaces. [1,2,[15][16][17][18][19][20] One prime example of such an interface is the LaAlO 3 /SrTiO 3 (LAO/STO) heterointerface where the polar nature of LAO induces charge transfer into the neighboring STO, generating a 2D-electron-gas (2DEG) at the interface of the two nominally insulating compounds. [15,[21][22][23] Free electrons are generated without local dopants.…”
Section: Doi: 101002/adma202004132mentioning
confidence: 99%